Synthesis of 2'-fluorinated-2'-deoxycytidine derivatives to investigate a direct DNA demethylation pathway in stem cells - Ponkkonen, Eveliina (2018)
This master’s thesis is divided into a literature review and an experimental part. The literature review starts with an introduction of nucleic acids and epigenetics, covering both chemical- and biological aspects. These chemical- and biological processes are explained at a level that is needed to understand the aim of the experimental project and the purpose of the synthesized compounds. The main focus of this thesis is the 2’-deoxyribonucleic acid, especially 2’-deoxycytidine derivatives being in the leading role. The roles and functions of other components, like purine bases and histones, are not included in this thesis. The latter part of the literature review, concerning the chemistry of 2’-deoxy pyrimidines and respective 2’-fluorinated derivatives, introduces their chemical properties. Based on the published data, this review will summarize different chemical approaches to introduce a variety of functional groups to the C5-postion of the pyrimidine ring to obtain C5 functionalized- 2’-deoxyuridine and 2’- deoxycytidine derivatives. In the experimental part, the main objective was to synthesize 5-nitro-2’-fluoro2’-deoxycytidine and 5-(butyl-4-acetoxy-benzoate)-2’-fluoro-2’-deoxycytidine to study their roles in the active demethylation process that occurs via C–C bond cleavage. The last steps of the latter mentioned compound requires further optimization and therefore remains under work. 5-Nitro-2’-fluoro-2’-deoxycytidine was further studied by feeding it to cultured mammalian cells. For the detection of its potential incorporation into DNA, UHPLC-MS/MS was used to provide quantitative data. The analysis showed no incorporation occurred into the DNA, however the nucleoside was found in the soluble pool and therefore, could have other biological implications. This thesis gives a brief insight into the challenging field of chemical biology that is not studied during the master courses but is explained in the understandable manner for the students on master level. It will be of interest to an audience of multidisciplinary researchers in organic- and biological chemistry and it can be helpful for entering chemists to understand the chemical aspects concerning epigenetics and nucleoside chemistry as well as their connection to biology.